Preliminary Results of HEARTS - Vinall, Phil (MD Conference Express, 2011)
The HEart function Assessment Registry Trial in Saudi Arabia [HEARTS] is a nationwide medical registry of heart failure (HF) throughout Saudi Arabia. The goal of the registry is to study practice patterns in the management of patients with acute HF to assess the gap between practice and evidence, to improve the quality of cardiac care that is provided, and to establish heart function clinics across the country that will reduce the morbidity and mortality of HF disease by appropriately managing high-risk chronic HF patients.